Cold Water Immersion as a Method Supporting Post-Exercise Recovery - Kowalski, M.; Lubkowska, A. (Central European Journal of Sport Sciences and Medicine, 2022)
The aim of the study was to assess the effect of cold water immersion on changes in blood lactate concentration during post-exercise recovery in swimmers subjected to2-minute exercise test (front crawl swimming movements) using a VASA Swim Ergometer, with the maximum arm speed movements, as during the freestyle technique. The study covered 11 professional swimmers of the MKP Szczecin club, tested twice with a two-week interval. Each participant performed an exercise test twice, once with a passive recovery period, and the second time with cold water immersion after exercise, as a method potentially supporting the post-exercise recovery process. Each time before the test, immediately after and at 3, 6 and 9 minutes after exercise, the concentration of lactate in the capillary blood was measured. Statistical analysis of the obtained results showed that cold water immersion applied immediately after exercise resulted in a faster reduction of lactate concentration. The conducted research confirms that cold water immersion used in post-exercise recovery may be an effective method of restoring optimal physical fitness as part of the training process.